Asian Pacific Society of Cardiology Consensus Recommendations for Pre-participation Screening in Young Competitive Athletes - Luokai Wang; Tee Joo Yeo; Benedict Tan; Bernard Destrube; Khim Leng Tong; Swee Yaw Tan; Gregory Chan; Zijuan Huang; Frankie Tan; Yu Chen Wang; Jong-Young Lee; Erik Fung; et al. (European Cardiology Review)
Sports-related sudden cardiac death is a rare but devastating consequence of sports participation. Certain pathologies underlying sports-related sudden cardiac death could have been picked up pre-participation and the affected athletes advised on appropriate preventive measures and/or suitability for training or competition. However, mass screening efforts – especially in healthy young populations – are fraught with challenges, most notably the need to balance scarce medical resources and sustainability of such screening programmes, in healthcare systems that are already stretched. Given the rising trend of young sports participants across the Asia-Pacific region, the working group of the Asian Pacific Society of Cardiology (APSC) developed a sports classification system that incorporates dynamic and static components of various sports, with deliberate integration of sports events unique to the Asia-Pacific region. The APSC expert panel reviewed and appraised using the Grading of Recommendations Assessment, Development, and Evaluation system. Consensus recommendations were developed, which were then put to an online vote. Consensus was reached when 80% of votes for a recommendation were agree or neutral. The resulting statements described here provide guidance on the need for cardiovascular pre-participation screening for young competitive athletes based on the intensity of sports they engage in.